Fenomena Pendidikan Keagamaan Masyarakat Tabanan Bali : Kasus Majelis Taklim Al-Falah - Abd. Muin M (Badan Litbang dan Diklat Kementerian Agama RI, 2008)
This research is done in order to describe the characteristic of religion board as the effort in redesigning it, so that the religion board is more able in giving the feasibility service with the needs of its follower today and in the future. This quantitative research is done to al-Falah religion board in Moslem minority territory in sub province of Tabanan Bali. The finding of the research calls that al-Falah religion board as the unit of non-formal religious education, has been grow highly in the minority Moslem people community as the effort in fulfilling the needs of Moslem people itself. Meanwhile from the management side it is lack handled professionally mainly in arranging education program and material that is not guiding to the needs of its follower real yet. This matter can effect to the possibility that the follower will leave the religion board.